A multicenter retrospective analysis of clinical outcomes of intracranial chondrosarcoma in 26 patients - Hongyuan Liu; Zongping Li; Yafei Xue; Tianzhi Zhao; Yingxi Wu (Scientific Reports, 2023)
Abstract Intracranial chondrosarcoma is a rare tumor with limited reports. We reviewed the clinical outcomes, imaging findings, and pathological characteristics at three centers to improve the diagnosis and treatment of intracranial chondrosarcoma. We retrospectively analyzed 26 patients with intracranial chondrosarcoma who had undergone surgical treatment at Tangdu Hospital of Air Force Military Medical University, Mianyang Central Hospital, and Nanchong Central Hospital from January 2010 to July 2022. Clinical manifestations, imaging features, surgical treatment, prognosis, and overall survival (OS) were analyzed. All 26 chondrosarcomas were located at the skull base. Gross total resection (GTR), subtotal resection (STR), and partial resection (PR) were performed in 14, 10, and 2 cases, respectively. Four cases underwent endoscopic transnasal surgery, while the remaining cases underwent craniotomy. The clinical symptoms were evaluated 1 week after surgery, and 15 cases were relieved to varying degrees. Postoperative complications included pulmonary infection, subcutaneous hydrops, dysphagia and choking, facial numbness, abducens paralysis, and intracranial infection (ICI). Fifteen cases received postoperative adjuvant radiotherapy. Seven cases showed recurrence: two with PR, four with STR, and one with GTR. Six cases received reoperation or radiotherapy after tumor progression, and one untreated patient died 5 months after tumor recurrence. The extent of tumor resection (HR 21.74, 95% CI 1.25–376.6, P = 0.03) and pathological grading (HR 131.99, 95% CI 4.05–4300.5, P = 0.006) were associated with improved OS. We presented our experience in the treatment of intracranial chondrosarcoma at three centers in the past 12 years. Intracranial chondrosarcoma lacked typical imaging features and are difficult to differentiate from other skull base lesions. Maximum extent of tumor resection with minimal injury to neurological function remains the most important treatment strategy. The extent of surgical resection and pathological grading were found to be predictors for OS.